2018
DOI: 10.1080/20009666.2018.1483693
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected deterrent in diagnosing refractory celiac disease and enteropathy-associated T-cell lymphoma: a gluten-free diet

Abstract: Enteropathy-associated T-cell lymphoma (EATL) is a rare disease found in the small bowel and is seen most commonly in patients with refractory celiac disease (RCD). We present a case of an elderly male with celiac disease (CD) diagnosed in childhood with months of abdominal pain and diarrhea despite attempting to avoid gluten in his diet. After persistent symptoms for months, the patient was admitted for an acute abdomen and was found to have small bowel perforation due to a jejunal mass that was diagnosed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Intestinal lymphomas are believed to be one of the leading causes of death in patients with CD diagnosed in adulthood [ 3 ]. The incidence of lymphoma is much greater in the sixth, seventh, and eighth decades of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal lymphomas are believed to be one of the leading causes of death in patients with CD diagnosed in adulthood [ 3 ]. The incidence of lymphoma is much greater in the sixth, seventh, and eighth decades of life.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphomas generally follow a highly aggressive clinical course and have a poor prognosis [ 9 ]. EATLs can also present in disseminated forms with the involvement of mesenteric lymph nodes, the liver, spleen, lungs, and skin [ 3 ]. EATLs should be suspected in patients with elevated LDH and β2microglobulin, anemia, a BMI of around 18, and low serum albumin levels [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It has been reported that approximately 70% of patients with CD have symptomatic remission within 2 weeks after starting a GFD. 2 Herein, this case report presents a patient with recurrent CD due to a discontinuation of GFD. When the CD recurred, the patient developed fever and pancytopaenia, and quickly died of haemophagocytic lymphohistiocytosis (HLH).…”
Section: Introductionmentioning
confidence: 99%